Ti3+-O Acid–Base Pairs for Efficient Solar-Driven Photothermal Nonoxidative Ethane Dehydrogenation - Yuwen Sun; Kun Gong; Tianyu Li; Yunlei An; Qiwen Sun; Tiejun Lin; Liangshu Zhong (Journal of the American Chemical Society, 2026)
Abstract Nonoxidative ethane dehydrogenation (NOEDH) is a carbon efficient but thermodynamically severe route for ethene production. Solar-driven NOEDH offers a promising alternative, yet achieving both high activity and high ethene selectivity over noble metal-free catalysts without external heating remains unresolved. Here, we reported that Ti3+-O acid–base pairs on reduced rutile TiO2 enabled highly efficient full-spectrum solar-driven photothermal NOEDH without any external heating. The optimally reduced TiO2 at 750 °C delivered an ethene production rate of 392.0 mmol g–1 h–1, which was 1107 times higher than that of pristine TiO2 without reduction pretreatment. The high activity with a C2H4 selectivity of 94.9% surpassed the thermodynamic equilibrium limit and outperformed previously reported systems. Comprehensive characterizations identified surface Ti3+ sites adjacent to lattice oxygen as Lewis acid–base pairs that enhanced light absorption, promoted charge carrier separation, and directly participated in the C–H bond cleavage. Photogenerated electrons also preferentially accumulated on the coordinatively unsaturated Ti3+-O sites, which weakened ethene adsorption, thereby accelerating product desorption and suppressing deep dehydrogenation and coke formation. The synergy between photogenerated hot carriers and localized photothermal heating lowered the apparent activation energy from 157.6 kJ mol–1 in the dark to 75.0 kJ mol–1 under illumination. This work establishes surface acid–base pairs on noble metal-free catalyst as a powerful platform for sustainable light-driven alkane upgrading.